2023
DOI: 10.3390/app132212125
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Two Different Competition Models on Physical Performance in Under-13 Basketball Players: Analysis Considering Maturity Timing

Ricardo André Birrento-Aguiar,
Jorge Arede,
Nuno Leite
et al.

Abstract: The rules of team sport have been influenced by professional competitions without considering all the factors that differentiate children and adolescents from adults. The aim of this study was to analyse the performance of kinematic variables in two different types of tournaments and the influence of somatic maturation on performance in young basketball players. Thirty-seven under-13 male basketball players (age = 12.91 ± 0.57 years) were selected by four southeast Spanish teams to participate in two different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…In this sense, there is a large amount of scientific evidence that states that the level of maturity stage influences technical aspects such as ball control, dribbling, or passing [ 36 ]; physical aspects such as endurance, strength, and flexibility [ 37 ]; and executive functions [ 38 ]. Thus, only the study by Birrento et al [ 39 ] was found. This work shows that basketball players at an early maturity stage have better cinematic performance than players at a late development stage.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, there is a large amount of scientific evidence that states that the level of maturity stage influences technical aspects such as ball control, dribbling, or passing [ 36 ]; physical aspects such as endurance, strength, and flexibility [ 37 ]; and executive functions [ 38 ]. Thus, only the study by Birrento et al [ 39 ] was found. This work shows that basketball players at an early maturity stage have better cinematic performance than players at a late development stage.…”
Section: Introductionmentioning
confidence: 99%